Female photojournalist discrimination during the Covid-19 pandemic in Indonesia - Sarwono, Billy; Yasak, Ellen M.; Ajidarma, Seno Gumira; Asteria, Donna (Faculty of Communications Science, Dr. Soetomo University, 2023)
The development of news about Covid-19 that hit almost the entire world, was conveyed massively by the mass media. The work process of journalists in reporting makes them vulnerable to infection. Photojournalists have to rack their brains to keep sending news. During the pandemic, female photojournalists experienced more obstacles and discrimination than before the pandemic. A strong patriarchal system gives rise to gender discrimination in the male-dominated photojournalist profession. This research is qualitative research with a critical paradigm. Researchers want to see the extent of discrimination against three female photojournalists in Indonesia during the pandemic. This research used qualitative methods, with semi-structured interviews, to explore the experiences of female photojournalists during the Covid-19 pandemic. The findings of this study are the existence of double burden gender discrimination, maternal discrimination, and layoff for those who have high salaries (discrimination based on pay) from the media where they work.